Coping strategies among caregivers of people with Alzheimer disease: a systematic review - Monteiro,Alexandre Magno Frota (2018)
Abstract Introduction Caregivers of people with Alzheimer disease (PwAD) report significant stress, burden and depression compared to caregivers of people with other dementias, especially when neuropsychiatric symptoms are prominent. Adequate coping strategies can modify the impact of stressful situations and increase the caregivers’ quality of life. Objective To systematically review the different coping strategies used by caregivers of PwAD to manage neuropsychiatric symptoms. Method We carried out electronic searches using MEDLINE (PubMed), SciELO, Web of Knowledge Cross Search (Thomson Scientific/ISI Web Services) and PsycINFO databases to select studies on coping in PwAD caregivers published from January 2005 to July 2017. The search terms were coping, caregivers, strategy, onset, adaptation, family, behavior, dementia and Alzheimer. The studies were organized in three categories: problem-focused, emotion-focused and dysfunctional coping strategies. Results We found 2,277 articles. After application of exclusion criteria and exclusion of redundant references, 24 articles were analyzed. Emotion-focused coping was the most commonly used strategy among PwAD caregivers. The use of this strategy associated with religion and spirituality may help reduce symptoms of depression and anxiety. Problem-focused coping strategies were mostly used with active coping interventions. Problem-solving coping may have buffered the impact of acute psychological stressors on procoagulant activity. Dysfunctional coping strategies were associated with increase of caregiver burden. Conclusion The evaluated studies showed that the use and development of coping strategies may have ameliorated the depressive symptoms, anxiety and burden of caregivers. However, longitudinal studies are still needed that clearly describe the type of coping strategy used in relation to the presented results.